The Development of English Differentiated Teaching Modules at 7 Grade Junior High School 3 Tebo - Cenby Rosella Agustin Ellbas; Diana Oktavia; Winda Trisnawati (Proceedings Series on Social Sciences & Humanities, 2024)
This study aimed to develop the differentiated learning Modul as one of English teaching instruments. As it is required to fulfill one of Merdeka Curriculum characteristics, especially the differentiated learning. This differentiated learning module was designed and developed based on students’ learning styles (auditory, visual and kinesthetic) and students’ talents and interests. This study was conducted using Research and Development method with ADDIE development model. The module development was focused on the series of differentiated learning modules for English in 7 graders. After conducting the analysis, design, and development. The differentiated learning module was validated in term of material and media. The average result in the material validation test was 87,5 % in the very valid category, while the media validation test was 89,5% in the very valid category. Furthermore, the product practicality was found through the questionnaires and product trial observation. The questionnaires were used to find out the perspective of teacher and students toward this developed module. It was found that the module was feasible to be used with the percentage 95,82% for teacher’s questionnaire and 99,15% for students’ questionnaire. Moreover, observation sheet result showed that this differentiated learning module was feasible with the percentage 90,85%.